The impact of school enterprise cooperation and vocational skills training on the employment competitiveness of vocational collage students in Yunnan Province - Wang, Aiqi; Traiwannakij, Surachai (Proceeding of International Conference on Islamic Education (ICIED), 2024)
This article combines literature review and questionnaire survey methods to systematically examine the theoretical framework and development status of school-enterprise cooperation and vocational skills training. Research has shown that school enterprise cooperation can promote the integration of educational resources and market demand, provide more internship opportunities, enhance students' professional ethics and practical abilities, and thus improve their employment competitiveness. Enterprise participation enables vocational colleges to promptly understand industry development trends, adjust course offerings, optimize teaching content, and better meet enterprise talent needs. As an essential component of vocational education, vocational skills training offers targeted courses and practical training programs to help students master skills that meet industry standards and enhance their adaptability to the job market. Finally, this article concludes that school-enterprise cooperation and vocational skills training are essential means to improve the employment competitiveness of vocational college students. By deepening school enterprise cooperation and strengthening vocational skills training, students' vocational abilities and comprehensive qualities can be effectively improved, helping them better adapt to the rapidly changing job market. Vocational colleges should fully leverage their core role in talent cultivation, closely collaborate with enterprises, and jointly promote the development of high-quality vocational education.